The main mechanism of the innovation economy of innovation infrastructure . (Journal of Economic Research & Business Administration, 2015)
In this article , the basic mechanism of the innovation economyinnovative infrastructure as important issueson condition capable of forming.Each state has its own national innovation infrastructureIt attaches great importance . Innovation can bäsekegeq ékonomïkanıqIt is an important factor in the formation .
Keywords: Innovative infrastructure; innovative economy